Implementasi Pemberian Izin Usaha Untuk Menunjang Kegiatan Usaha (PB UMKU) Setelah Berlakunya Online Single Submission (OSS) di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu (DPMPTSP) Provinsi Jambi - Vinda Cahyani Putri; Wahyu Adi Mudiparwanto (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The aim of this research is to find out and analyze Business Licensing to Support Business Activities (PB UMKU) after the implementation of Online Single Submission (OSS) in Jambi Province and to find out and analyze the obstacles to implementing OSS in Granting Business Permits in Jambi Province. The research method used is a combination of normative legal and empirical legal research types, based on data obtained directly from the community, such as observations, interviews and questionnaires. The research approach that the author uses is by researching and reviewing in depth information related to business licensing in (DPMPTSP) Jambi Province. Research analysis uses descriptive-qualitative techniques, to prepare and strengthen the author's arguments. The author's results and findings in this research show that (PB UMKU) in its implementation (OSS) in Jambi Province is in accordance with applicable regulations, although there are several obstacles in overcoming it, it is in accordance with Minister of Home Affairs Regulation Number 24 of 2006 concerning Guidelines for the Implementation of Integrated One Door. The conclusion of this research is, (DPMPTSP) Jambi Province has made maximum efforts to implement Online Single Submission (OSS) and overcome all existing obstacles based on relevant applicable regulations.